Recent Advances in Ligand-Controlled Regio- or Stereodivergent Transition-Metal-Catalyzed Hydroelementation (H[E]) (E = H, B, Si, Ge) of C–C Unsaturated Systems - Park, Sehoon (Synthesis, 2024)
Reductive functionalization of C–C unsaturated systems, including alkenes and alkynes, with a range of hydroelements (H[E]) is one of the most fundamental and highly practical methods for the synthesis of functionalized hydrocarbons. Since the resultant hydrocarbon products have strong applicability as synthetic intermediates, numerous homogeneous organo(metallic) catalysts have been intensively utilized to date for reductive functionalization reactions. In particular, well-defined transition-metal-based catalysts capable of controlling the regio- or stereoselectivity of a product by harnessing the addition of H[E] (E = H, B, Si, Ge) into Cα–Cβ unsaturated bonds have drawn special attention. In this review, we describe recent examples of transition-metal catalytic systems (M = Fe, Co, Rh, Pd, Ni) for regio- or stereodivergent hydroelementation reactions of (conjugated) alkenes, alkynes, and allenes to give a pair of isomeric products in high selectivities from the same starting compounds simply by variation of the ligand. Mechanistic aspects of the ligand-controlled selectivity divergence are discussed in detail on the basis of experimental observations and/or computational insights.1 Introduction2 Hydroelementation of Alkenes and Alkynes3 Hydroelementation of Conjugated Dienes and Diynes4 Hydroelementation of Allenes5 Summary and Outlook
Keywords: transition-metal catalysis; hydroelementation; regiodivergence; stereodivergence; ligand effect; C–C unsaturated systems